2015
DOI: 10.1002/eji.201445340
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering allogeneic antibody response against native and denatured HLA epitopes in organ transplantation

Abstract: Anti-HLA donor-specific antibodies are deleterious for organ transplant survival. Class I HLA donor-specific antibodies are identified by using the Luminex single antigen beads (LSAB) assay, which also detects anti-denatured HLA antibodies (anti-dHLAs). Anti-dHLAs are thought to be unable to recognize native HLA (nHLA) on the cell surface and therefore to be clinically irrelevant. Acid denaturation of nHLA on LSAB allows anti-dHLAs to be discriminated from anti-nHLAs. We previously defined a threshold for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The clinical significance of these “natural” antibodies is a matter of debate and studies revealed conflicting results, even though the clinical impact might be rather limited . Interestingly, one study reported that antibodies against denatured HLA antigens may also be able to bind to intact HLA molecules .…”
Section: Technical Challenges and Limitationsmentioning
confidence: 99%
“…The clinical significance of these “natural” antibodies is a matter of debate and studies revealed conflicting results, even though the clinical impact might be rather limited . Interestingly, one study reported that antibodies against denatured HLA antigens may also be able to bind to intact HLA molecules .…”
Section: Technical Challenges and Limitationsmentioning
confidence: 99%
“…Still another concern regarding MFI values stems from interferences due to antibody-dependent complement activation. However, Visentin et al reported that sera from some patients contain antibodies to both native and denatured HLA antigens of the same specificity or specificities (13). These events can artifactually diminish MFI values to well below a cutoff threshold.…”
Section: Be Prepared To Stop: Limitationsmentioning
confidence: 99%
“…The limited data published on this topic suggest that reactivity to denatured proteins does not contribute to poor graft outcome (11). However, Visentin et al reported that sera from some patients contain antibodies to both native and denatured HLA antigens of the same specificity or specificities (13). Thus, unless and until reactivity to native and denatured HLA antigens can be easily discerned, it is premature to consider reactivity to denatured antigens as clinically innocuous.…”
Section: Be Prepared To Stop: Limitationsmentioning
confidence: 99%
“…[11][12][13][14][15][16] However, detection of serum DSA with SAFB has technical limitations, falsenegative and false-positive results being respectively caused by complement interference [17][18][19] and by anti-HLA antibodies of ill-defined pathogenic role recognizing denatured class I HLA molecules. [20][21][22][23][24][25] The presence of DSA is not synonymous with lung allograft injury. 26 The lack of direct association may be due to the inability of the DSA to bind to the graft because of the absence of expression of cognate HLA molecules, or because of insufficient binding strength between a low affinity DSA and its target.…”
Section: Introductionmentioning
confidence: 96%